ANALISIS KETERAMPILAN SERVIS DAN PASSING PADA SISWA EKSTRAKURIKULER BOLA VOLI SMP N 2 RANTAU PANDAN - Maryulian; Maulana Putra, Ikhsan (Jurnal Muara Olahraga, 2024)
Abstract This research was motivated by the unknown level of students' skills in basic volleyball techniques. This research aims to determine the top serve, bottom serve, top pass and bottom pass skills of extracurricular volleyball students at SMPN 2 Rantau Pandan t. This research is a qualitative descriptive study. The sampling technique used purposive sampling, the sample in this study was volleyball extracurricular students with a total of 16 students. Data collection techniques using tests. The test instrument used is the French-Choper. The analysis technique used is to put the frequency into percentage form. The results of this research show that the level of upper service skills is considered low considering that the highest frequency is in the low category with a total of 6 students, namely 38%. The level of lower service skills is considered sufficient considering that the highest frequency is in the sufficient category with a total of 8 students, namely 50%. The level of upper passing skills is considered poor considering that the highest frequency is in the poor category with a total of 6 students, namely 38%. The level of bottom passing skills is considered sufficient considering that the highest frequency is in the sufficient category with a total of 8 students, namely 50%. Key words: analysis, skills, serving, passing, volleyball